Nepotism in Post-Soviet States: The Quantitative Assessment on Socio-Demographic Factors and the Corruption Perceptions Index - Byulegenova , Bibigul; Prasolov, Valeriy; Sheryazdanova , Gulmira; Bratanovsky , Sergey; Sabirova, Lilya (Journal of Ethnic and Cultural Studies, 2024)
Nepotism has long been one of the global problems of modern society. In many countries, including the post-Soviet space, this phenomenon is firmly historically rooted. Granting privileges to relatives or friends, regardless of their professional qualities, destroys the institutional foundations of the state, causing significant harm to public administration and the economy. The purpose of the study is to examine the influence of cultural and ethnographic factors in form of socio-demographic factors and the level of acceptability of corruption on the development of nepotism against the background of corruption as an aggregate indicator of its manifestation. The research methodology was based on studying the socio-economic development indicators of 12 countries of the former Soviet Union according to the official data presented by the World Bank and the Transparency International organization. This research holds the view that the Corruption Perceptions Index can serve as an indirect indicator of the level of nepotism in the post-Soviet space. A study based on a regression model of the correlation of the described values of a quantitative model for assessing the level of penetration of nepotism in developing countries, including post-Soviet ones. The practical application of the results may make it possible to more deeply assess the features of the development of society and the state on the basis of generally recognized international indicators and available demographic data.